Functional fitness control by coach in cross-country skiing sport - Vlasova, V. P.; Ignatieva, L. E.; Komarova, N. A.; Mamaev, A. R. (Theory and Practice of Physical Culture, 2019)
The article analyzes the functional fitness control methods applicable by coaches in the elite cross-country skiing sport. Generally the competitive performance in elite cross-country skiing is determined by the cardio-respiratory system adaptability to the growing workloads, energy costs and efficiency of the body rehabilitation process. Sampled for the study were skilled cross-country skiers (n=12) from among the Physical Education Department students, qualified Class I to candidate masters of sport. The sample was tested by ergogenic L-carnitine `Elcar` (made by Peak Pharma Ltd.) administered in the moderate doses as recommended for the physical working capacity (PWC) building purposes. The group progress tests showed benefits of the additive as verified by the progress of the Experimental Group in the PWC and post-training rehabilitation indices. On the whole, the group was tested with the improved tolerance to the physical workloads and faster rehabilitation rates; and the finding gives grounds to recommend the L-carnitine administration scheme for application in the modern cross-country skiing sport.